English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

x^2 -5x + 6

2007-07-15 03:58:22 · 5 answers · asked by peaches 1 in Science & Mathematics Mathematics

5 answers

x^2 -5x + 6 = (x-2)(x-3)
----------
Ideas: You factor 6 into -2 and -3 such that -2+-3 = -5 the coefficient of the linear term -5x.

2007-07-15 04:01:16 · answer #1 · answered by sahsjing 7 · 0 0

x^2 - 5x + 6 = (x - 2) (x - 3)

How did we get the factors? Easy.

Look at 6, it can be expressed as 1 multiplied by 6 or 2 multiplied by 3. Now, which of them make 5 when we add? 2 and 3. And sign has to be -2 and -3 so that the sum becomes - 5 and product + 6.

2007-07-15 11:05:33 · answer #2 · answered by Swamy 7 · 0 0

This is a quadratic equation, with simple ''Middle-term splitting'' factorization.
x^2 - 5x + 6 can be written as:
= x^2 - 2x - 3x + 6 (split the middle term into 2 factors
= x(x-2) -3(x-2) of the constant 6)
= (x-3)(x-2)

Hope that helps.

2007-07-15 11:05:50 · answer #3 · answered by Apoorv 2 · 0 0

x^2 -5x + 6
=x^2 -2x -3x + 6
=x(x-2) - 3(x-2)
=(x-3)(x-2)

2007-07-15 11:04:20 · answer #4 · answered by fofo m 3 · 0 0

(x-2 )(x-3 )

2007-07-15 11:02:42 · answer #5 · answered by CPUcate 6 · 0 0

fedest.com, questions and answers